Pengetahuan Pasien tentang Karies Gigi di Poli Gigi Puskesmas Kangayan Kepulauan Kangean - Mardlatillah, Lutviana; Isnanto, Isnanto; Sugito, Bambang Hadi (FORIKES, 2025)
The main oral health problem among dental clinic patients is dental caries. A lack of understanding of the etiology of dental caries can contribute to its development. The purpose of this study was to determine the level of understanding of dental caries among dental clinic patients. This descriptive study focused on dental caries among dental clinic patients at the Kangayan Community Health Center in the Kangean Islands. Data were collected through questionnaires, which were then analyzed using descriptive statistics in the form of frequencies and percentages. The findings of this study indicate that the highest level of patient understanding for each component of knowledge is as follows: the importance of dental caries is in the good category (82%), the causes of dental caries are in the sufficient category (73%), the impact of dental caries is in the sufficient category (60%), the prevention of dental caries is in the sufficient category (67%), and the treatment of dental caries is in the low category (48%). It can be concluded that the level of knowledge of dental clinic patients about dental caries at the Kangayan Community Health Center in the Kangean Islands is in the sufficient category.Keywords: dental caries; patients; dental clinic; knowledge ABSTRAK Masalah kesehatan gigi dan mulut yang utama pada pasien poli gigi adalah karies gigi. Kurangnya pemahaman tentang etiologi karies gigi dapat menyebabkan perkembangannya. Tujuan dari penelitian ini adalah untuk mengetahui tingkat pemahaman tentang karies gigi pada pasien di poli gigi. Penelitian ini merupakan studi deskriptif yang berfokus pada karies gigi pada pasien poli gigi di Puskesmas Kangayan di Kepulauan Kangean. Data dikumpulkan melalui pengisian kuesioner, yang selanjutnya dianalisis dengan metode statistika deskriptif berupa frekuensi dan persentase. Temuan penelitian ini menunjukkan Tingkat pemahaman pasien yang paling besar pada masing-masing komponen pengetahuan adalah sebagai berikut: pentingnya karies gigi dalam kategori baik (82%), penyebab karies gigi dalam kategori cukup (73%), dampak karies gigi dalam kategori cukup (60%), pencegahan karies gigi berada dalam kategori cukup (67%), terapi karies gigi dalam kategori rendah (48%). Dapat disimpulkan bahwa tingkat pengetahuan pasien klinik gigi tentang karies gigi di Puskesmas Kangayan Kepulauan Kangean berada pada kategori cukup.Kata kunci: karies gigi; pasien; poli gigi; pengetahuan